2021
DOI: 10.1021/acsabm.0c01576
|View full text |Cite
|
Sign up to set email alerts
|

Fused-Ring Small-Molecule-Based Bathochromic Nano-agents for Tumor NIR-II Fluorescence Imaging-Guided Photothermal/Photodynamic Therapy

Abstract: Optical imaging in the second near-infrared (NIR-II) windows reduces much more autofluorescence and photon scattering from biological tissues and allows further tissue penetration depth and superior spatial resolution in living bodies. Herein, a fused-ring 2,2′-((2Z,2′Z)-((12,13-bis(2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]thiadiazolo[3,4-e]thieno[2,″3″:4′,5']thieno-[2′,3′:4,5]pyrrolo[3,2-g]thieno[2′,3′:4,5]thieno[3,2-b]indole-2,10-diyl)bis(methanylylidene))bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In 2021, many groups, including our own, demonstrated that Y6 has good anti-tumor activities based on the combination of PDT and PTT (Table 3). [175][176][177] In addition, Tian's group systematically studied the effects of the side chains in Y-series photosensitizers on their PTT performance. 178 The flexible side chains are more facile to rotate than the rigid side chains, which have big effects on the photothermal conversion.…”
Section: Advances In Small-molecule Photosensitizers With A-d-a Struc...mentioning
confidence: 99%
“…In 2021, many groups, including our own, demonstrated that Y6 has good anti-tumor activities based on the combination of PDT and PTT (Table 3). [175][176][177] In addition, Tian's group systematically studied the effects of the side chains in Y-series photosensitizers on their PTT performance. 178 The flexible side chains are more facile to rotate than the rigid side chains, which have big effects on the photothermal conversion.…”
Section: Advances In Small-molecule Photosensitizers With A-d-a Struc...mentioning
confidence: 99%
“…Another SM TPBT was explored, and there was no NIR‐II fluorescence when dispersed in an organic solvent. [ 79 ] However, TPBT could form the J ‐aggregates by nanoprecipitation. TPBT NPs had a NIR‐II emission shoulder, which was enough for NIR‐II FLI.…”
Section: Imaging‐mediated Cancer Therapymentioning
confidence: 99%
“…When NIR-II light passes through tissues, the interaction between photons and tissues is significantly reduced, and the photons can penetrate into deeper tissues, so as to achieve better surgical guided anatomy (Figure 1b). For this purpose, various NIR-II emissive fluorescent probes, such as metal nanoparticles [16][17][18], inorganic semiconductor nanoparticles [19,20], small molecular-based nanoparticles [20,21], and aggregation-induced emission (AIE) nanoparticles [22,23], have been established. Very recently, semiconducting polymer dots (Pdots) have attracted extensive attention for in vivo fluorescence imaging applications [24].…”
Section: Introductionmentioning
confidence: 99%